The appropriate nutrient conditions for methicillin-resistant Staphylococcus aureus and Candida albicans dual-species biofilm formation in vitro - Vávrová, Pavlína; Janďourek, Ondřej; Diepoltová, Adéla; Nachtigal, Petr; Konečná, Klára (Scientific reports, 2025)
Polymicrobial biofilms, the reason for most chronic wound infections, play a significant role in increasing antibiotic resistance. The in vivo effectiveness of the new anti-biofilm therapy is conditioned by the profound evaluation using appropriate in vitro biofilm models. Since nutrient availability is crucial for in vitro biofilm formation, this study is focused on the impact of four selected cultivation media on the properties of methicillin-resistant Staphylococcus aureus and Candida albicans dual-species biofilms. To reflect the wound environment, Tryptic soy broth, RPMI 1640 with and without glucose, and Lubbock medium were supplemented with different amounts of host effector molecules present in human plasma or sheep red blood cells. The study demonstrates that the Lubbock medium provided the most appropriate amount of nutrients regarding the biomass structure and the highest degree of tolerance to selected antimicrobials with the evident contribution of the biofilm matrix. Our results allow the rational employment of nutrition conditions within methicillin-resistant Staphylococcus aureus and Candida albicans dual-species biofilm formation in vitro for preclinical research. Additionally, one of the potential targets of a complex antibiofilm strategy, carbohydrates, was revealed since they are prevailing molecules in the matrices regardless of the cultivation media.
Keywords: živiny; Methicillin-Resistant Staphylococcus aureus; Anti-Bacterial Agents; ovce; Candida albicans; biofilmy; Microbial Sensitivity Tests; Animals; zvířata; Biofilms; Humans; Nutrients; antibakteriální látky; methicilin rezistentní Staphylococcus aureus; kultivační média; Sheep; mikrobiální testy citlivosti; lidé; Culture Media